DSGE Models and Central Banks - Camilo Ernesto Tovar (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
Over the past 15 years there has been remarkable progress in the specification and estimation of dynamic stochastic general equilibrium (DSGE) models. Central banks in developed and emerging market economies have become increasingly interested in their usefulness for policy analysis and forecasting. This paper reviews some issues and challenges surrounding the use of these models at central banks. It recognises that they offer coherent frameworks for structuring policy discussions. Nonetheless, they are not ready to accomplish all that is being asked of them. First, they still need to incorporate relevant transmission mechanisms or sectors of the economy; second, issues remain on how to empirically validate them; and finally, challenges remain on how to effectively communicate their features and implications to policy makers and to the public. Overall, at their current stage DSGE models have important limitations. How much of a problem this is will depend on their specific use at central banks.
Keywords: B4; C5; E0; E32; E37; E50; E52; E58; F37; F41; F47; 330; DSGE models; central banks; communication m; estimation; modelling; Dynamisches Gleichgewicht; CGE-Modelling; Geldpolitik; Transmissionsmechanismus; Schätztheorie; Theorie